Successful treatment of a patient aged 1 month with long QT syndrome and multiple episodes of ventricular fibrillation - S. Yu. Prorok; O. S. Proidak; M. S. Meshkova; O. V. Doronin; N. M. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2018)
Long QT syndrome (LQTS) is a rare condition associated with sudden cardiac death. Accumulation of experience of the successful management of patients under the age of 1 year old with LQTS is a relevant issue.Objective. To analyse the com-plex case of treatment of a patient with LQTS.Materials and methods. Treatment of a symptomatic patient aged 1 month with LQTS was performed.Results and discussion. We have a successful experience of epicardial pacing in combination with β-blockers.Conclusion. Prescription of β-blocker maximal doses and epicardial pacing is the efficient treatment method in patients under 1 year of age with LQTS and unstable hemodynamics.